Delivery of public health interventions by the ambulance sector: a scoping review - Suzanne Ablard; Elisha Miller; Steven Poulton; Anna Cantrell; Andrew Booth; Andrew Lee; Suzanne Mason; Fiona Bell (BMC, 2023)
Abstract Background With millions of unscheduled patient contacts every year and increasing call outs clustered around the most deprived communities, it is clear the ambulance sector could have a role to play in improving population health. However, the application and value of a public health approach within the ambulance sector has not been comprehensively explored. A scoping review was undertaken to explore the role of the ambulance sector in the delivery of public health interventions and what impact this has on population health and ambulance sector outcomes. Methods A search strategy was developed on MEDLINE and translated to other major medical and health related bibliographic databases (Embase; CINAHL; HMIC; Science and Social Sciences Citation Index; Cochrane Library) to identify literature published since 2000 in OECD countries. Targeted grey literature, reference list, and citation searching was also carried out. Search results were downloaded to Microsoft Excel and screened by three reviewers according to pre-determined inclusion / exclusion criteria. Data from included studies, such as the type of activity noted within the paper, the population involved and the public health approach that was utilised, was extracted from within the paper using a data extraction form and narratively synthesised. Results Fifty-two references were included in the final review (37 database searching; 9 reference list searching; 6 grey literature). Included articles were categorised according to the relevant public health domains and subdomains as articulated by the UK Faculty of Public Health: 1. Health improvement domain: Public health education and advice (Health promotion sub-domain) (n=13) Emergency Services personnel providing vaccines (Disease prevention sub-domain) (n=1) 2. Health care public health domain Paramedicine (Service delivery sub-domain) (n=30) Screening tools and referral pathways used by the ambulance sector (Service delivery sub-domain) (n=28) Health intelligence using ambulance sector data (population health management sub-domain) (n=26) Of note, some domains (e.g. health protection) returned nil results. Discussion The scoping review demonstrates the breadth of public health related activities in which the ambulance sector is involved. However, an overemphasis on demand management outcomes precludes definitive conclusions on the impact of ambulance sector-led public health initiatives on public health outcomes. Future evaluations of public health initiatives should incorporate wider health system perspectives beyond the immediately apparent remit of the ambulance sector.